Investigation of possibility of creation of levitating quadrupole - Bishaev, A.M.; Bush, A.A.; Gladyshev, I.V.; Kamentsev, K.Y.; Kozintseva, M.V. (Вопросы атомной науки и техники, 2011)
The configuration of the supporting magnetic field for the levitation of two superconducting rings is developed. It has been formed experimentally from four permanent coaxial magnets of N40 grade inserted one into another with alternate poles and having one common external surface. The ceramics rings form high-temperature superconductive (HTSC) phase Y-123 of proper sizes demonstrating superconducting properties with the critical current sufficient for their levitation have been manufactured. The existence of stable equilibrium positions for two superconducting rings with the current in the supporting magnetic field and in the field of the gravity force has been experimentally proved. Based on carried out experiments and calculations the configuration of the laboratory model of the levitating quadrupole has been proposed. Розроблена конфігурація підтримувального магнітного поля для левітації двох надпровідних кілець. Експериментально вона сформована з чотирьох співвісних магнітів марки N40, вкладених один в одного з чергуванням полюсів і що мають одну загальну зовнішню поверхню. Виготовлені керамічні кільця з високотемпературної надпровідної (ВТНП) фази Y-123 відповідних розмірів, що проявляють надпровідні властивості з критичним струмом, достатнім для їх левітації. Експериментально доведено існування стійких рівноважних станів для двох надпровідної кілець із струмом в підтримувальному магнітному полі і в полі сили тяжіння. На підставі проведених експериментів і розрахунків запропоновано конфігурацію лабораторної моделі левітуючого квадруполя. Разработана конфигурация поддерживающего магнитного поля для левитации двух сверхпроводящих колец. Экспериментально она сформирована из четырех соосных магнитов марки N40, вложенных друг в друга с чередованием полюсов и имеющих одну общую внешнюю поверхность. Изготовлены керамические кольца из высокотемпературной сверхпроводящей (ВТСП) фазы Y-123 соответствующих размеров, проявляющие сверхпроводящие свойства с критическим током, достаточным для их левитации. Экспериментально доказано существование устойчивых равновесных состояний для двух сверхпроводящих колец с током в поддерживающем магнитном поле и в поле силы тяжести. На основании проведенных экспериментов и расчетов предложена конфигурация лабораторной модели левитирующего квадруполя.